PKM Pengembangan Aplikasi Perpajakan Berbasis Web Untuk Usaha Mikro Kecil Dan Menengah (UMKM) - Denni Pratama; Fadhil Muhamad Basysyar; Irfan Ali; Yudhistira Arie Wijaya; Rina Andriyanti (CV. Multi Kreasi Media, 2022)
The development of information technology has had a significant impact on various sectors, including taxation. Small and Medium Enterprises (SMEs) in Indonesia often face difficulties in managing their taxes due to a lack of knowledge and limited resources. Therefore, this research aims to develop a web-based taxation application that can assist SMEs in managing their taxes more efficiently and accurately. The methodology used in the development of this application includes the stages of needs analysis, system design, implementation, and testing. The result of this research is a user-friendly web-based taxation application that can facilitate SMEs in tax calculation, reporting, and payment automatically. This application is expected to improve tax compliance among SMEs and reduce errors in the tax reporting process. Thus, this application has the potential to be a practical solution for SMEs to tackle taxation challenges in the digital era.